Blue sail come cover - Lodge-Rigal, Susannah, author; Beachy-Quick, Dan, advisor; Steensen, Sasha, committee member; Little, Ann, committee member (Colorado State University. Libraries, 2020)
Blue Sail Come Cover is a study of love—an investigation of care blurred by fear and gratitude, a searching for sign in world and word, both. These poems explore conditions of loss and fear, and within those wounds, the necessity of love and its manifestations—patience and care. This manuscript's central personas, a lyric I and a lyric you, encounter omen, song, and the sky's changeable weather, ever in search and in awe of a more companionable world. As they move through geographies of memory, grief, fear, and the American Midwest in search of a kinder ontology, they discover a means by which to stay. While explicit internal and external landscapes remain legible throughout, these poems are rooted most by their assertions of how care can keep us. As the I and you transform across the three sections, they attend to silence and song within themselves and in their environment, eventually discovering a more welcoming world. This manuscript explores how attention—to the world, each other, and the lyric—can enact the sort of faith that helps people stay. In Blue Sail Come Cover, the objective isn't to solve life's big questions, but to learn how to live with them. It is a book of discovery, slowly uncovering its own ethos for living and dwelling, for caring for one another through every joy, sorrow, and ordinary day. It is my hope, then, that these poems are first and foremost companionable—that the I and you who occupy these pages are participants in the very world we live in. In this project, I am interested in troubling the I/thou tradition and seeing what these pronouns can accomplish when freed from static identities. These pages formally and substantively probe lyric tropes—I/thou, sky, birds, song—in an attempt to unearth larger questions surrounding the trouble and necessity of a lyric voice.